A Study on the Visual Symbols of the Guangdong Awakening Lion’s Head Mask - Sudan, Zhan (Universiti Malaysia Sarawak, 2024)
Lion dance, an ancient cultural symbol deeply embedded in Chinese heritage, particularly in Guangdong Province, boasts a unique and rich visual language. This research explores the visual symbols and elements within the lion dance masks of Guangdong, revealing the profound cultural, traditional, and artistic expressions they embody. The primary objective is to establish a comprehensive and reliable data framework of visual symbols associated with Guangdong lion dance masks, serving as a valuable resource for government agencies, traditional culture researchers, artistic creators, and industry professionals. This framework will lay the theoretical foundation for the effective protection, promotion, and development of this cherished cultural heritage. Employing a multifaceted approach, the study combines literature review, interviews, field investigations, theoretical analysis, image analysis, and comparative methods to meticulously examine the visual symbols of lion dance masks. This comprehensive approach provides a holistic overview of the visual landscape of lion dance masks across four distinct regions within Guangdong Province. Through a semiotics approach, the study unravels the intricacies and diversity of Guangdong lion dance culture, shedding light on its rich cultural significance and values. A thorough analysis of the visual symbols embedded within Guangdong lion dance masks, juxtaposed with existing literature and interviewee perspectives, reveals inconsistencies and gaps in the available documentation. Consequently, this study systematically addresses these shortcomings, filling the void in knowledge within this domain. This research serves as a cornerstone for future scholarly endeavors dedicated to Guangdong lion head culture. To fully harness its potential for cultural preservation, transmission, and global recognition, the government should implement appropriate measures. Such initiatives will undoubtedly empower this research to contribute significantly to the safeguarding, perpetuation, and international dissemination of China’s rich cultural heritage.